2015
DOI: 10.1111/gwat.12316
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Cycling in Hydrocarbon Plumes: Secondary Effects of Natural Attenuation

Abstract: Monitored natural attenuation is widely applied as a remediation strategy at hydrocarbon spill sites. Natural attenuation relies on biodegradation of hydrocarbons coupled with reduction of electron acceptors, including solid phase ferric iron (Fe(III)). Because arsenic (As) adsorbs to Fe-hydroxides, a potential secondary effect of natural attenuation of hydrocarbons coupled with Fe(III) reduction is a release of naturally occurring As to groundwater. At a crude-oil-contaminated aquifer near Bemidji, Minnesota,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 41 publications
7
91
0
Order By: Relevance
“…Our results are generally similar to the well‐studied groundwater plume emanating from a very large biodegrading crude oil release near Bemidji, Minnesota, USA, where the “non‐volatile dissolved organic carbon” in the low‐oxygen shadow downgradient of the dissolved hydrocarbon plume 1) extends farther than the dissolved hydrocarbons and 2) is primarily composed of organic acids (Eganhouse et al ; Essaid et al ; Cozzarelli et al ). The overall scale and associated anaerobic geochemical footprint of the Bemidji release is larger than the sites we studied, and the Bemidji source is crude oil whereas our study focused on refined fuels.…”
Section: Discussionsupporting
confidence: 84%
“…Our results are generally similar to the well‐studied groundwater plume emanating from a very large biodegrading crude oil release near Bemidji, Minnesota, USA, where the “non‐volatile dissolved organic carbon” in the low‐oxygen shadow downgradient of the dissolved hydrocarbon plume 1) extends farther than the dissolved hydrocarbons and 2) is primarily composed of organic acids (Eganhouse et al ; Essaid et al ; Cozzarelli et al ). The overall scale and associated anaerobic geochemical footprint of the Bemidji release is larger than the sites we studied, and the Bemidji source is crude oil whereas our study focused on refined fuels.…”
Section: Discussionsupporting
confidence: 84%
“…Others (Amirbahman et al ; He et al ; Hering et al ) have observed natural attenuation of As with the formation of Fe and Mn oxides as the groundwater moves into oxic sediments away from the biostimulated treatment zone. Likewise, Ziegler et al () and Ziegler et al () noted redistribution of As along the flow path in a crude‐oil contaminated sandy aquifer in Bemidji, Minnesota, with As being retained with distance from the plume by sorption of Fe oxides (Cozzarelli et al ). Amirbahman et al () described the role of Mn oxides in the oxidation of As(III) and natural attenuation of the produced As(V) through sorption.…”
Section: What Happened To the As Within The Columns?mentioning
confidence: 98%
“…Choosing the source of organic carbon and how much to add are critical decisions when attempting efficient dechlorination, but may be counter to controlling As mobilization. These considerations would also be relevant to many other plumes, where the biodegradation of organic materials coupled with reduction of Fe(III) oxides releases As to the groundwater within the biologically active zone, but attenuation would occur with distance from the plume, as observed at the leading edge of a crude‐oil plume in Bemidji, Minnesota (Cozzarelli et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Except for sulfate, potential electron acceptors for anaerobic BTEX degradation like nitrate and reactive Fe(III) were low . However, ponds contain iron oxides in clay minerals (Kaminsky et al, 2008) presumably available for BTEX metabolisation (Cozzarelli et al, 2015). In addition, BTEX can be biodegraded during respiration with humic acids (Cervantes et al, 2001) and under methanogenic conditions (Grbic-Galic and Vogel, 1987).…”
Section: Role Of Organic Carbon and Srb On Btex Turnovermentioning
confidence: 99%